Influences of Tobacco-Related Knowledge on Awareness and Behavior towards Smoking - Park, Jinju (J Korean Med Sci, 2018)
BACKGROUND: A considerable amount of research has shown that knowledge and appropriate awareness are essential for encouraging positive behaviors and promoting health. In Korea, the roles that behavioral changes play in the prevention of cancer have been an important issue since the introduction of the 10 codes for cancer prevention in 2006. Thus, the present study investigated the associations of tobacco-related knowledge with awareness and attitudes towards positive smoking-cessation behaviors. METHODS: The present study analyzed data from the 2010 national questionnaire survey (n = 1,006). This study evaluated sociodemographic characteristics, smoking status, self-rated health status, health-related interests, and the accuracy of 12 tobacco-related statements to determine knowledge level and to investigate its impact on awareness and behaviors related to smoking. These parameters were examined and staged using the Precaution Adoption Process Model. RESULTS: A higher level of tobacco-related knowledge was significantly associated with a positive attitude towards smoking cessation (5–8 correct answers: odds ratio [OR], 2.53; 95% confidence interval [CI], 1.57–4.08; ≥ 9 correct answers: OR, 3.90; 95% CI, 2.22–6.82; reference: ≤ 4 correct answers). Interestingly, among current smokers, only those who correctly responded to ≥ 9 of 12 tobacco-related statements were significantly associated with a positive attitude towards smoking cessation. CONCLUSION: This study found that having a higher level of tobacco-related knowledge had a significant impact on positive attitudes towards smoking cessation. This suggests that there is a need to disseminate appropriate knowledge to the general population to encourage positive attitudes and promote healthful behaviors in terms of smoking.